INCLUSIVE SEXUAL EDUCATION FROM THE PERSPECTIVE OF TEACHERS: ANALYSIS OF THE PORTUGUESE AND BRAZILIAN CONTEXT - Bortolozzi, Ana Claudia [UNESP]; Spadotto de Carvalho, Leilane Raquel [UNESP]; Vilaca, Teresa (Fundacao Univ Tocantins, 2020)
This descriptive research investigated and compared the conceptions of 48 teachers in Brazil and 45 in Portugal about sexuality and sexual education (SE) of students from special education in inclusive public schools, who answered a questionnaire for quantitative analysis. In both countries, teachers observed behaviors in students: questions about sexuality, kisses, dating and curiosities common to other young people, but also inappropriate behaviors such as touching their own bodies publicly and from other people. They consider the students uninformed about sexuality and their sources of information to be family members and internet (Portugal) and teachers and family members (Brazil). They are in favor of SE at school, believe that it is their role to do this, but they do not feel prepared. The data were similar in both contexts, in spite of the fact that SE is law in Portugal and not in Brazil, and we concluded that teacher training would be necessary for inclusive sexual education.
Keywords: Sexual Education; Inclusion; Teacher Training; Special Education